Role of Heuristic Principles On Crowd-Funder's Investment Decision Making - Willy Das; Satyasiba Das (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
With the rise in entrepreneurial activities, the study of a firm's fund generation strategy is widely discussed and researched. The requirement of funds for different ventures are different and depends on the life stage of the venture, which it is in. The firm generally faces difficulty in raising outside capital-both debt and equity. Crowdfunding is a fairly recent fund generating method that reduces this financial gap. Crowdfunding involves individuals who decide whether or not to invest in a project. Since it involves decision making under uncertainty we probe the possibility of the presence of heuristic principles in the decision-making process. We propose that certain heuristic principles like availability and representativeness affect the decision-making process of the investors. Thus, this paper aims to explore the "fast and frugal" way of decision-making in crowd funders. Building on the existing literature of decision making under risk and uncertainty, cognitive models, beha vioural finance and theories of entrepreneurial finance, we propose that heuristic principles come to play in case of crowdfunding and since the amount invested is pretty small and does not cause a major loss, people do not go for exhaustive mental taxation and instead opt for the fast and frugal way of decision-making that is achieved by using heuristic principles. The managerial implication of this paper lies in the biases that arise due to the usage of heuristic principles which has been extensively discussed in the paper. Hence, is useful for both the entrepreneurs (in designing the pitch) and the crowd-funders (making wise investment decisions).
Keywords: 650; Crowdfunding; Heuristic principles; Availability; Representativeness; Cognitive model